2019
DOI: 10.3390/molecules24010176
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gelatin Supplemented with Gum Arabic, Tween 20, and β-Cyclodextrin on the Microencapsulation of Turkish Oregano Extract

Abstract: Microencapsulation protects core materials from deteriorating due to environmental conditions, such as moisture or oxidation, and improves the bioavailability of active compounds, allowing one to make solid formulations from oils and increase their solubility. Wall and core material properties determine the microencapsulation efficiency and the best results are achieved when a wall material mixture is used to prepare the microcapsules. In this work, we optimized the wall material composition (gelatin supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…31 However, the encapsulation efficiency value in our study was higher than the values obtained by Abarca et al, who reported a 34.8% encapsulation efficiency of ⊎-cyclodextrin and volatile oil. 32 In addition, the microencapsulation efficiency of 55.14% was lower than the 80.65% reported by Baranauskaite et al 33 The difference in microencapsulation efficiency may be because of the difference in the time and temperature of air drying, as different drying methods have previously been shown to play an important role in the microencapsulation efficiency of essential oils. 34 Morphological characteristics of the microcapsules Scanning electron microscopy photographs of ⊎-cyclodextrin and the microcapsules are shown in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…31 However, the encapsulation efficiency value in our study was higher than the values obtained by Abarca et al, who reported a 34.8% encapsulation efficiency of ⊎-cyclodextrin and volatile oil. 32 In addition, the microencapsulation efficiency of 55.14% was lower than the 80.65% reported by Baranauskaite et al 33 The difference in microencapsulation efficiency may be because of the difference in the time and temperature of air drying, as different drying methods have previously been shown to play an important role in the microencapsulation efficiency of essential oils. 34 Morphological characteristics of the microcapsules Scanning electron microscopy photographs of ⊎-cyclodextrin and the microcapsules are shown in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Solid formulation techniques (e.g., microencapsulation, liposomes, nanoparticles) are used for their controlled release and targeted delivery of such hydrophobic oils [57,58,59,60]. Such techniques also address additional issues related to essential oils and their terpenoid constituents (strong odor, taste, evaporation, degradation, and sensitivity to light, air, and temperature) [61].…”
Section: Discussionmentioning
confidence: 99%
“…The most common process used is spray drying, due to its low cost, easy scale-up and applicability with a wide range of core and wall materials, delivering the encapsulated materials as a powder with particles generally a few micrometers in size. It has been used, for example, to encapsulate phenolic compounds from spent espresso coffee [110]; olive leaf extracts [138]; citrus by-product extracts [139]; apple fruit peel [140]; pigments from wine by-products [141]; carotenoids from tomato pomace [72]; essential oils from herbs, such as oregano [142,143,144], and lavender [145]; and vitamins [146].…”
Section: Stabilization Processesmentioning
confidence: 99%
“…Extracts from agricultural by-products have shown great potential to be incorporated in packaging materials, with promising results. Baranauskaite and Kopustinskiene [143], prepared chitosan films with an ethanolic mango leaf extract (MLE) having antioxidant properties. When applied as packaging materials for cashew nuts’ storage, fatty acid oxidation was reduced by 56% for the nuts stored with 5% MLE film compared to commercial, non-biodegradable polyamide/polyethylene (PA/PE) films.…”
Section: Applications In the Food Industrymentioning
confidence: 99%